A nomogram model based on preoperative grey-scale US features and routine serum biomarkers to predict the outcome of infants with biliary atresia after Kasai portoenterostomy - Weng, Zongjie; Ye, Fengying; Zhou, Luyao; Chen, Fa; Ling, Wen; Fang, Yifan; Liu, Min; Wu, Qiumei; Qiu, Xiuqing; Lyu, Guorong (Frontiers in Pediatrics, 2022)
Objective To establish a nomogram to predict the outcome of biliary atresia (BA) infants 3-months post- Kasai portoenterostomy (KPE). Methods BA Infants who underwent KPE from two hospitals were included in the training (n=161) and validation cohorts (n=64). A logistic regression equation (Equation A) for predicting the serum total bilirubin (TBIL) level 3-month post-KPE was established in the training cohort. Then, a nomogram was developed based on Equation A in the training cohort and validated in the validation cohort. Moreover, a new equation (Equation B) was generated based on the nomogram and the size of the enlarged hilar lymph nodes (LNs) in the validation cohort. The predictive performance of the nomogram was evaluated by the receiver operating characteristic (ROC) curve and by calculating the area under the ROC curve (AUC), sensitivity, specificity, and positive (PPV) and negative (NPV) prediction values. Results A nomogram based on gallbladder morphology and serum levels of TBIL and total protein (TP) was established with AUC of 0.673 and 0.647, sensitivity of 71.4% and 81.8%, specificity of 63.3% and 47.6%, PPV of 81.6% and 45.0%, and NPV 49.2% and 83.3%, respectively, in the training and validation cohorts. Furthermore, in the validation cohort, the AUC of Equation B was 0.798, which was significantly higher than that of the nomogram (P=0.042). Conclusion A nomogram based on the pre-KPE gallbladder morphology, TBIL, and TP to predict the outcome of BA 3-months post-KPE is established. Moreover, the addition of the size of the enlarged hilar LNs into the nomogram further improves its predictive value.